2007
DOI: 10.1097/01.ypg.0000242201.56342.1a
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of illicit drug use and transition to dependence in Southwest California Indians

Abstract: These findings suggest that heritability of the initiation of substance use, in Southwest California Indians, may be similar to other population samples. In this population, however, high rates of dependence on marijuana, opiates, and stimulants are seen once initiation of the use of the substance has occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
4
22
0
1
Order By: Relevance
“…First, these fi ndings are relevant to theories attempting to explain the high rates of cannabis and other drug misuse among Native Americans living on reservations. Among these theories, some researchers have suggested that the increased rates of drug dependence within this population can be attributed to early exposure (Ehlers et al, 2007) and a lack of contingency between access to basic life reinforcers (e.g., employment, education, housing) and sobriety (Spillane and Smith, 2007). The reported result that the socially contingent abuse symptoms represent more severe symptoms among Native Americans than European Americans suggests that social contingencies are more frequently violated in the presence of heavy cannabis use among European Americans and less so among Native Americans living on reservations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, these fi ndings are relevant to theories attempting to explain the high rates of cannabis and other drug misuse among Native Americans living on reservations. Among these theories, some researchers have suggested that the increased rates of drug dependence within this population can be attributed to early exposure (Ehlers et al, 2007) and a lack of contingency between access to basic life reinforcers (e.g., employment, education, housing) and sobriety (Spillane and Smith, 2007). The reported result that the socially contingent abuse symptoms represent more severe symptoms among Native Americans than European Americans suggests that social contingencies are more frequently violated in the presence of heavy cannabis use among European Americans and less so among Native Americans living on reservations.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a larger study examining the etiology of substance use disorders in a community sample of American Indians living on reservations (see Ehlers et al, 2001Ehlers et al, , 2004Ehlers et al, , 2007Gilder et al, 2004Gilder et al, , 2009), the present study applied IRT methods to accomplish two specifi c aims: (a) to evaluate whether cannabis misuse symptoms assess a continuous latent trait that indexes the severity of cannabis use in both Native Americans living on reservations and European Americans and (b) to evaluate whether individual cannabis misuse symptoms differentially index severity in these two populations. Because the Native American community under study has been shown to exhibit very high rates of substance use disorders (e.g., 70% alcohol dependent, 60% cannabis dependent), we chose to use an equally affected population of European Americans for the present report, the University of California, San Francisco (UCSF) Family Alcoholism Study population (70% alcohol dependent, 44% cannabis dependent), which is a nationwide population-based sample selected for the presence of alcohol dependence (Ehlers et al, 2010).…”
mentioning
confidence: 99%
“…The lifetime prevalence of substance dependence in this Indian population is high and evidence for heritability and linkage to specific chromosome locations and associations with candidate genes has been demonstrated (see Wall et al, 2003; Ehlers et al, 2004b, 2006b, 2007a,b,c, 2008a,b, 2009a,b, 2010a; Ehlers and Wilhelmsen, 2005, 2007; Wilhelmsen and Ehlers, 2005). The current study’s aims were to: (1) map loci linked to SRE phenotypes and (2) to determine if there was overlap of the loci identified for SRE phenotypes and loci previously mapped for alcohol and other substance dependence in this American Indian community.…”
Section: Introductionmentioning
confidence: 94%
“…The discrete traits were modeled with a liability threshold model. These analyses have been described previously (Ehlers et al, 2004a(Ehlers et al, , 2006Wilhelmsen and Ehlers, 2005).…”
Section: Data Analysesmentioning
confidence: 99%